Determinant of Labor Force Resilience Against The Employment Impact of The Covid-19 Pandemic in Bali Province, Indonesia: An Application of Survival Analysis - Ni Luh Putu Yayang Septia Ningsih; Mohammad Dokhi (Proceedings of The International Conference on Data Science and Official Statistics, 2021)
The impact of coronavirus disease 2019 (Covid-19) pandemic is not only on health problems, but also has a negative impact on economic. The sector that economically worst affected by the pandemic is the tourism and its derivatives. As a result of depending heavily on the tourism sector, Bali is the province with the most labor force that has stopped working during the pandemic. In this study, data from the national labor force survey were analyzed using the Weibull-Gamma Shared Frailty Survival Model to explore the determinants of labor force resilience against the event of stop working due to the Covid-19 pandemic. The results show that gender, education level, experience in training, marital status, and age of labor force are variables that significantly affect on how quickly a labor force experiences an event of stop working. Moreover, variations among regions where they work (regencies/cities) also have a significant effect on stop working acceleration.